Transformasi Digital Dalam Manajemen Pendidikan: Meningkatkan Efisiensi dan Aksesibilitas - Lazwardi, Dedi; Kurinawan, M. Agus (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2025)
Digital transformation in educational management became an urgent necessity in the modern era, particularly after the global pandemic accelerated the adoption of digital technologies in the education sector. This study examined the implementation of digital transformation in educational management, focusing on improving operational efficiency and accessibility to educational services. Using both qualitative and quantitative approaches, the research analyzed data from 50 educational institutions that had implemented digital transformation in their management systems. The findings indicated that digital transformation significantly contributed to a 45% increase in administrative efficiency, a 60% acceleration in decision-making processes, and a 75% improvement in the accessibility of educational services for stakeholders. Key challenges identified included resistance to change, infrastructure limitations, and the need for staff training. This research provided valuable insights for educational institutions considering or currently undergoing the implementation of digital transformation in their management systems.